Lula's second act - Hunter, W; Power, TJ (Johns Hopkins University Press, 2023)
A highly polarized Brazilian electorate went to the polls in October 2022. Workers' Party candidate and former president (2003–2010) Luiz Inácio Lula da Silva narrowly defeated far-right incumbent president Jair Bolsonaro, while unprecedented numbers of right-wing candidates won seats for the National Congress as well as governorships across Brazil. Constitutionalism prevailed, defying concerns that the illiberal Bolsonaro would reject an electoral loss and call upon the military to back an antisystem challenge. Although a democratic alternation in power will occur, governance will be difficult. Lula will not enjoy the political and economic conditions that facilitated the successful governance strategies he employed previously.